Entrepreneurial Business Ties and New Venture Growth: The Mediating Role of Resource Acquiring, Bundling and Leveraging - Gang Wang (Sustainability, 2019)
Adopting insights from a resource management perspective, this study investigates how entrepreneurs utilize their business ties to promote new venture growth. We propose a multiple mediator model in which different resource management processes (i.e., resource acquiring, resource bundling, and resource leveraging) act as critical mediating mechanisms. We undertook a two-stage survey design, and collected data during the period from 2013 to 2016. Drawing on a longitudinal sample of 229 new ventures in China, we tested the hypotheses through the optimal scaling regression (OSR) analysis. We find empirical support for the mediated effects of entrepreneurial business ties via resource bundling and resource leveraging to promote new venture growth. However, our results find the mediating effect of resource acquiring non-significant. These findings will deepen understanding of the role of entrepreneurial business ties in the new venture growth process and expand resource management perspective into the entrepreneurial field.